Development of sensitizer peptide-fused endolysin Lys1S-L9P acting against multidrug-resistant gram-negative bacteria - Son, Su Min; Kim, Joonbeom; Ryu, Sangryeol (Frontiers in Microbiology, 2023)
The advent of multidrug-resistant (MDR) bacteria poses a major threat to public health, garnering attention to novel antibiotic replacements. Endolysin, a bacteriophage-derived cell walldegrading enzyme, is a promising alternative to conventional antibiotics. However, it is challenging to control Gram-negative bacteria due to the presence of the outer membrane that shields the peptidoglycan layer from enzymatic degradation. To overcome this threshold, we constructed the fusion endolysin Lys1S-L9P by combining endolysin LysSPN1S with KL-L9P, a sensitizer peptide known to extend efficacy of antibiotics by perturbing the outer membrane of Gram-negative bacteria. In addition, we established a new endolysin purification procedure that increases solubility allowing a 4-fold increase in production yield of Lys1S-L9P. The sensitizer peptide-fused endolysin Lys1S-L9P exhibited high bactericidal effects against many MDR Gram-negative pathogens and was more effective in eradicating biofilms compared to LysSPN1S. Moreover, Lys1S-L9P showed potential for clinical use, maintaining stability at various storage temperatures without cytotoxicity against human cells. In the in vivo Galleria mellonella model, Lys1S-L9P demonstrated potent antibacterial activity against MDR Gram-negative bacteria without inducing any toxic activity. This study suggest that Lys1S-L9P could be a potential biocontrol agent to combat MDR Gram-negative bacteria.